Timing and Mechanisms of the Formation of the Dark Layers in the Sea of Japan During the Last 40 kyr - Gorbarenko, S.; Shi, X.; Bosin, A.; Liu, Y.; Artemova, A.; Zou, J.; Yanchenko, E.; Vasilenko, Y.; Wu, Y.; Hu, L. (Frontiers in Earth Science, 2021)
The marginal location of the Sea of Japan and its constrained water exchange with the western Pacific make this sea a subtle subject for the investigation of orbital and suborbital climate changes. However, the response of this unique basin to the climate and sea level changes at the end of the last glaciation and deglaciation and during the Holocene is not fully understood. We provided detailed reconstructions of the dark layers (DLs), including the timing and mechanisms responsible for their formation, during the last 40 kyr, based on the multiproxy correlation of three cores from the northern and central parts of the sea with well-dated δ18O records of the Greenland ice and China cave stalagmites. High resolution color photo lightness, the conventional color parameters L* and b*, AMS 14C data, chlorin and carbonate calcium content and pollen climate parameters allowed the correlation of the DLs of these cores with Greenland interstadials (GI), Heinrich stadials (HS) and summer East Asian monsoon intensity. DLs 9, 8, 7 and 6, formed after HS 4 (38.5–39.5 ka), were triggered by GIs 8, 7, 6 and 5, coeval with the intensification of the East Asian summer monsoon and the increase of surface water stratification and productivity. The long-lasting GI 8, accompanied by significant climate warming, led to the formation of the more intense DL 9. The accumulation of DL 5 was forced by a rapid global sea level fall, coeval with cold HS 3, due to the decrease of saline Tsushima Current water input into the sea, increased surface water stratification and a drop in deep water ventilation. DL 4 was probably launched by GI 3 and summer East Asian monsoon intensification. Further falls in global sea level during the last glacial maximum led to the formation of DLs 3 and 2 during the periods 27.0–24.2 ka and 23.5–17.0 ka, respectively. DL 1 was associated with significant summer East Asian monsoon intensification and environmental warming at the onset of the Holocene.